The Bible and Moral Injury: Reading Scripture Alongside War's Unseen Wounds - Kelle, Brad E. (Abingdon Press, 2020)
Cover -- Half title -- Title -- Copyright -- Dedication -- Contents -- Foreword -- Preface and Acknowledgments -- 1. Introduction -- Unseen Wounds, Moral Injury, and Scripture -- Starting Points -- The Bible and Moral Injury: A Two-Way Conversation -- Moral Injury as a Frame of Reference -- Biblical Interpretation's Contributions to Moral Injury Work -- Overview -- 2. Moral Injury and Biblical Interpretation -- Understanding Moral Injury (Definitions, Symptoms, and Healing) -- Definitions -- Causes and Effects -- A Theological Conception of Moral Injury -- Healing and Repair -- Moral Injury and Biblical Texts: Past Work and Present Trajectories -- Past and Present Engagements -- Trajectories for Moving Forward -- 3. Moral Injury and the Case of King Saul (1 Samuel 9-31) -- Background: Ancient Texts, Literary Characters, and Moral Injury -- King Saul, the Morally Wounded Warrior -- The Experiences of Moral Injury -- The Consequences of Moral Injury -- Moral Injury Connections -- 4. Moral Injury and the Bible's Postwar Rituals -- Background: Postwar Rituals, Symbolic Practices, and Moral Injury -- Postwar Rituals of Return and Reintegration in the Old Testament and Its Context -- Return and Reintegration in the Old Testament -- Purification of Warriors, Captives, and Objects -- Appropriation of Booty -- Construction of Memorials and Monuments -- Return and Reintegration Outside the Old Testament -- Summary -- Moral Injury Connections -- Conclusion -- 5. Moral Injury, Lament, and Forgiveness -- Postwar Rituals of Celebration and Procession in the Old Testament and Its Context -- Moral Injury, the Needs of Soldiers, and the Practices of Lament -- Old Testament Lament -- Moral Injury Connections -- Honesty -- Forgiveness -- Community -- 6. Injured by the Bible: Do the Biblical Warfare Texts Morally Injure Their Readers?.